Elimination of Plasmids from Several Bacterial Species by Novobiocin - McHugh, Gail L. (1977)
Certain plasmids can be eliminated by exposure to growth-inhibiting concentrations of novobiocin. Novobiocin cured 8 of 14 plasmids (13 R-plasmids and an F′ lac) among one or another of four different bacterial hosts.